Image of the head of an education institution - Markova, V.; Knіazіeva, V. (Problems of Engineer-Pedagogical Education, 2023)
The article defines the importance of considering the concept of the image of the head of an education institution, the structure of the image, and directly the features of the image of the head of an education institution as one of the components of the popularity of the education institution. The problems of creating a positive image of the manager are analyzed. The leader's image is a coherent, uncontroversial image of the leader in the minds of others and subordinates, which corresponds to the goals, norms and values accepted in the organization, and expectations of the leader. Findings show that many factors are involved in the process of the image formation, some of which are primary, and the others are secondary. Primary factors act at the first meeting with the manager, precede secondary factors in time and make up the primary, or perceptual, stage of the image formation. Secondary factors continue contributing to the image during long-term interaction with the manager, are often associated with a deeper knowledge of their personality by subordinates, and constitute the secondary, or active, stage of the image formation. The secondary stage of the image formation reflects the characteristic features of managerial activity and includes the following elements: professional and personal qualities, abilities, knowledge and skills of the head of a state institution, their communication and behavior system. Based on the consideration and analysis of the concept of the image of the head of an education institution, the structure of the image is determined. Characteristics of the image of the head of an education institution are noted. The specificity of the image of the head of an education institution was studied and the main components are noted: professionalism and competence; dynamism, quick reaction in different situations, active engagement; moral reliability of the manager; the ability to influence people with deeds, words and appearance; humanitarian education; psychological culture of the manager. Taking into account the above, it was determined that the main characteristics of the head of an education institution include successful performance of their managerial functions, compliance with business etiquette and the culture of communication with heads of other education institutions, colleagues, subordinates and superiors from the Ministry of Education and Science of Ukraine, as well as creation and maintenance of their own positive image, which is a system of ideas about the manager, their activities and the power they hold, etc.